Oral Mass of a Fetus Incidentally Found during Second Trimester: Ultrasound Survey and Postnatal Prognosis of the Baby - Huseyin Durukan; Savas Gundogan; Murside Çevikoğlu Kıllı; Talat Umut Kutlu Dilek (Case Reports in Obstetrics and Gynecology)
Ultrasound (USG) and magnetic resonance imaging (MRI) can be used to detect and evaluate the face and neck tumors during the in-utero period. We reported and discussed an oral mass which was diagnosed incidentally at mid-trimester exam and managed successfully.